Factors influencing tourist’s intention to travel for food-related tourism in Penang, Malaysia - Chong, Joe Yee; Goh, Jenny; Tan, Mei Qin; Teo, Khai Pin (2023)
Food tourism is not only an experience to enjoy delicious food but also a way of cultural exchange and exploration, it is able to enrich the sensory experience of travellers and give them a deeper understanding of the different flavours and food traditions around the world. As a result, food tourism has become a unique and fulfilling way to travel that many travellers pursue. The main purpose of this study is to determine whether the seven variables: novelty and variety, authentic local foods, interpersonal and culture, health concern, familiarity and eating habits, sensory and contextual pleasure, and food experience will affect the tourists with food-related behavioural intention. This survey was conducted by distributing questionnaires to the target respondents in 12 states in Malaysia and six foreign countries. In total, there with only 450 responses are acceptable. The data collected from the survey will be analyzed using the Statistical Package for the Social Sciences (SPSS) to conduct the pilot study and the full study. Moreover, our research has also used multiple regression analysis and single regression analysis to test the positive relationship between the dependent variable (food-related behavioural intention) and the independent variables (novelty and variety, authentic local foods, interpersonal and culture, health concern, familiarity and eating habits, sensory and contextual pleasure, and food experience). In this research, the seven independent variables (novelty and variety, authentic local foods, interpersonal and culture, health concern, familiarity and eating habits, sensory and contextual pleasure, and food experience) have a positive relationship with the dependent variable (food-related behavioural intention). Thus, the detailed results of the research will be further discussed in the chapters below.